Antagonistic Effects and Volatile Organic Compound Profiles of Rhizobacteria in the Biocontrol of Phytophthora capsici - José Luis Ávila-Oviedo; Carlos Méndez-Inocencio; María Dolores Rodríguez-Torres; María Valentina Angoa-Pérez; Mauricio Nahuam Chávez-Avilés; Erika Karina Martínez-Mendoza; Ernesto Oregel-Zamudio; Edgar Villar-Luna (Plants)
Phytophthora capsici is a devastating pathogen in horticultural crops, particularly affecting Capsicum annuum (pepper). The overuse of chemical fungicides has led to resistance development, necessitating alternative strategies. This study investigates the antagonistic effects of four rhizobacterial isolates (Bacillus sp., Pseudomonas putida, Bacillus subtilis, Bacillus amyloliquefaciens) against P. capsici, focusing on the production of volatile organic compounds (VOCs). Using in vitro dual culture assays, we observed a significant inhibition of mycelial growth and sporangia production, especially by B. subtilis and B. amyloliquefaciens. The GC-MS/SPME-HS analysis identified key VOCs responsible for these antagonistic effects. Our findings demonstrate that specific rhizobacteria and their VOCs offer a promising biocontrol strategy, potentially reducing the reliance on chemical fungicides and contributing to sustainable agriculture.